2014
DOI: 10.1111/sms.12275
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion: The impact of beliefs of health benefits, social relations and enjoyment on exercise continuation

Abstract: The aim of this study was to explore how and why participants in structured exercise intervention programs continue or stop exercising after the program is finished. We conducted four focus group interviews with four groups of middle-aged and elderly men (total n = 28) who had participated in exercise interventions involving playing either a team sport (football) or a more individually focused activity (spinning and crossfit). Our results show that different social, organizational and material structures inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
114
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 43 publications
(46 reference statements)
10
114
0
6
Order By: Relevance
“…Playing football seemed to give the participants more positive experiences of interaction during the activity, therefore giving more possibilities to satisfy the need for relatedness. It was also found that the technically focused nature of football offered more opportunities for the participants to experience feelings of competence than the fitness training (Nielsen, et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Playing football seemed to give the participants more positive experiences of interaction during the activity, therefore giving more possibilities to satisfy the need for relatedness. It was also found that the technically focused nature of football offered more opportunities for the participants to experience feelings of competence than the fitness training (Nielsen, et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…It was expected that participants in a team game would score overall higher on the self-determined forms of motivation, intrinsic motivation and EM identified regulation, than the participants in an individual physical activity (Nielsen, et al, 2014;Wilson, et al, 2006). No group differences in EM introjected regulation and external regulation were expected.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations